Human Adipose-Derived Mesenchymal Stem Cells Cryopreservation and Thawing Decrease α4-Integrin Expression - Ana Carolina Irioda; Rafael Cassilha; Larissa Zocche; Julio Cesar Francisco; Ricardo Correa Cunha; Priscila Elias Ferreira; Luiz Cesar Guarita-Souza; Reginaldo Justino Ferreira; Bassam Felipe Mogharbel; Venkata Naga Srikanth Garikipati; Daiany Souza; Mirian Perlingeiro Beltrame; et al. (Stem Cells International)
Aim. The effects of cryopreservation on adipose tissue-derived mesenchymal stem cells are not clearly documented, as there is a growing body of evidence about the importance of adipose-derived mesenchymal stem cells for regenerative therapies. The aim of this study was to analyze human adipose tissue-derived mesenchymal stem cells phenotypic expression (CD34, CD45, CD73, CD90, CD105, and CD49d), colony forming unit ability, viability, and differentiation potential before and after cryopreservation. Materials and Methods. 12 samples of the adipose tissue were collected from a healthy donor using the liposuction technique. The cell isolation was performed by enzymatic digestion and then the cells were cultured up to passage 2. Before and after cryopreservation the immunophenotype, cellular viability analysis by flow cytometer, colony forming units ability, differentiation potential into adipocytes and osteoblasts as demonstrated by Oil Red O and Alizarin Red staining, respectively. Results. The immunophenotypic markers expression was largely preserved, and their multipotency was maintained. However, after cryopreservation, the cells decreased α4-integrin expression (CD49d), cell viability, and number of colony forming units. Conclusions. These findings suggest that ADMSC transplanted after cryopreservation might compromise the retention of transplanted cells in the host tissue. Therefore, further studies are warranted to standardize protocols related to cryopreservation to attain full benefits of stem cell therapy.